His bundle pacing, learning curve, procedure characteristics, safety, and feasibility: Insights from a large international observational study. (2nd August 2019) - Keene, Daniel; Arnold, Ahran D; Jastrzębski, Marek; Burri, Haran; Zweibel, Steven; Crespo, Eric; Chandrasekaran, Badrinathan; Bassi, Sukhbinder; Joghetaei, Nader; Swift, Matthew; Moskal, Pawel; Francis, Darrel P; et al.
Abstract: Background: His‐bundle pacing (HBP) provides physiological ventricular activation. Observational studies have demonstrated the techniques' feasibility; however, data have come from a limited number of centers. Objectives: We set out to explore the contemporary global practice in HBP focusing on the learning curve, procedural characteristics, and outcomes. Methods: This is a retrospective, multicenter observational study of patients undergoing attempted HBP at seven centers. Pacing indication, fluoroscopy time, HBP thresholds, and lead reintervention and deactivation rates were recorded. Where centers had systematically recorded implant success rates from the outset, these were collated. Results: A total of 529 patients underwent attempted HBP during the study period (2014‐19) with a mean follow‐up of 217 ± 303 days. Most implants were for bradycardia indications. In the three centers with the systematic collation of all attempts, the overall implant success rate was 81%, which improved to 87% after completion of 40 cases. All seven centers reported data on successful implants. The mean fluoroscopy time was 11.7 ± 12.0 minutes, the His‐bundle capture threshold at implant was 1.4 ± 0.9 V at 0.8 ± 0.3 ms, and it was 1.3 ± 1.2 V at 0.9 ± 0.2 ms at last device check. HBP lead reintervention or deactivation (for lead displacement or rise in threshold) occurred in 7.5% of successful implants. There was evidence of a learning curve: fluoroscopy time and HBP capture threshold reduced with greater experience, plateauing after approximately 30‐50 cases. Conclusion: We found that it is feasible to establish a successful HBP program, using the currently available implantation tools. For physicians who are experienced at pacemaker implantation, the steepest part of the learning curve appears to be over the first 30‐50 cases.